Relacionamento e comunicação na era da informação: um estudo sobre as relações no twitter - Ferreira, Sérgio Rodrigo da Silva (2012)
Twitter is a online microblogging, launched in 2006, with updates (tweets) limited to 140 characters, allowing its use also on mobile devices like phones. The objective of this study was to characterize the relationships present in Twitter, including interpersonal relationships between individuals and groups and between the individual and society, from the contents of the updates posted and interviews with users of the platform. We used as reference the work of Robert Hinde, which emphasizes the study of basic descriptive relationships, considering its internal aspects and different levels of complexity, namely, interactions, relationships, groups and society. Also referenced theories from the analysis of social networks, such as the theory of small worlds, of weak ties and networks without scale. A qualitative research study consisted of two phases, the first documentary in nature, in which the posts were analyzed (n = 2000) of 200 users taking as criteria capixabas dialogue, theme and functionality in order to establish categories of relationship. The second phase consisted of interviews of users (n = 10) dealing with topics concerning the use of Twitter and its role in social relations of the participants, including their interpersonal relationships with groups and with society more broadly seeking to identify changes brought by Twitter for relationships. Data analysis led to the conclusion that settle on the platform two types of relationship. A first, in which Twitter is used as a device of external relationships social media reproducing its aspects and demands. A second, where relationships are based on the information exchange, in which the traded value in relationships is the quality of the content of the messages from subjective criteria of interest, preference and characteristics. In this relationship, the attraction is linked to users who have power over certain type of information that is valued by its influence leading to the notion of social capital. This value is user perceived second personal qualities, your network location and type of interactions that produces it must be capable of producing transfer actions and responses. Furthermore, it was found that the desired values in the network influence the production of interaction.